THE ROLE OF WOMEN AS HEADS OF HOUSEHOLDS IN ENHANCING FAMILY INCOME: AN ISLAMIC ECONOMIC PERSPECTIV - Yuni Cahyani; Agus Setiawan; A. Muslimin (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This research is motivated by the increasing number of women acting as heads of households. The emergence of this role is influenced by various factors, ranging from internal factors such as the death of a spouse, divorce, permanent disability due to accidents, or the absence of a husband, to external factors such as poverty, gender inequality, and economic demands. Women become heads of households because they possess stronger economic capacity than their partners or choose to live independently without a partner. This study uses a qualitative method, with data collection tools including field observations, interviews with women who are heads of households, and documentation. The data were then analyzed through data reduction, data presentation, and conclusion drawing. The results show that women as heads of households play a significant role in the economic sector, particularly in informal sectors such as trading, farming, fishing, and other small-scale businesses. Despite facing challenges such as limited access to business capital and difficulties in balancing work and household responsibilities, these women have successfully increased family income and maintained household economic stability. These findings indicate that despite numerous obstacles, the role of women as heads of households is essential in sustaining family welfare.